فلسفة الآنية في البلاطات الزخرفية الإسلامية:الردهة القرمانلية أنموذجا: The Philosophy of Utensils in Islamic Decorative Tiles: The Al Caramanli Vestibule as a Model - Eblao, Amira Mohamed Khalifa (Journal Al-Muqaddimah, 2023)
The Islamic decoration was known for its deep overlap and its association with the architecture of mosques. Islamic decoration is characterized by spirituality, deepening in the boundless and the interpenetration of its components between beginnings and endings. Islamic decoration has uniqueness in the symbolism nature, whether in colour or shape. Hence, this research attempts to delve into the knowledge of the religious and aesthetic philosophy of drawing utensils inside the ceramic tiles, specifically The Al Caramanli Vestibule and what it contains components and decorative elements. It also focuses on utensil elements, where we will discuss the nature and origin of ceramics in general, and then we will go through the aesthetics of Islamic ceramics and delve into the elements and components of The Al Caramanli Vestibule. Most of these points will be addressed through the decorations executed in The Al Caramanli Vestibule in the Red Saraya Museum in Tripoli - Libya. The result revealed that drawing utensils are nothing but an expression of the oneness of belief and culture when the Muslim artist deliberately put the hidden idea and manifest appearance of drawing utensils to appear in the form of symbols to remain over time evidence of the oneness of God Almighty. Through it, religious teachings can be disseminated in artistic ways.